DEVELOPMENT AND USE OF DIGITAL INTERACTIVE OBJECTS IN ELECTRONIC TEACHING MATERIALS: Received: 04th August 2021; Revised: 07th December 2021, 10th February 2022, 25th February 2022; Accepted: 28th February 2022 - Tkalich, Tatsiana; Makovskaja, Elena; Jaskevich, Svetlana; Silkovich, Yuri (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The article reveals the significance of creating flexible scenarios for individual lessons in modern education. Analysis of scientific publications and the existing experience of business education has shown the need to increase the role of organizing the interaction and communication between subjects of the learning process. Traditionally, these are webinars, binary lectures, virtual tutorials, creative activities, work in small groups, etc. The article defines digital interactive objects (DIO) as the means to apply various interactive teaching methods using e-learning technologies. Considering the DIO as a didactic teaching tool, we distinguish several interactivity levels of teaching tools that allow us to choose the required form of educational content and to achieve learning goals. In the current study, DIO of business education has been developed. They are represented by sets of interactive objects for the implementation of various interactive methods and didactic teaching techniques according to the certain pedagogical scenario of the distance learning course. The relevance of the new pedagogical and technological scenarios for DIO results in the development of algorithms and methodological recommendations to be used by organizing training sessions in economic and business disciplines.